Biocompatible ionic liquids: fundamental behaviours and applications - Gomes, Joana M. (2019)
Biocompatible ionic liquids (Bio-ILs) are an eco- and bio-friendly family of ionic liquids (ILs) useful in applications ranging from the electrochemical to the biomedical fields. The most promising strategies for their synthesis involve using molecules from bio-renewable sources as a basis for both the anionic and cationic counterparts of the Bio-ILs structure. Several studies have been conducted on Bio-IL properties, including their impact on the environment and health safety. Herein, we review progress and strategies towards the synthesis of Bio-ILs and address their ecotoxicological and biological impact. Furthermore, we discuss the impact of using these compounds in a diverse range of applications, with some insights toward their use in the development of improved technologies.